ANALISIS FAKTOR–FAKTOR YANG MEMPENGARUHI PROFITABILITAS PERBANKAN SYARIAH DI INDONESIA - Astohar Astohar (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2016)
The problem of this research is gap between some research variables thatwill be used. In this study the variables selected for additional variables is thevariable finance deposit ratio (FDR) which still occurs gap between researchersone with other researchers.The data to be used in the sample is obtained from thewebsite of Bank Indonesia as well as the bank's official website. The sample of thisresearch is taken by purposive sampling that is the method where the sampleselection on the characteristics of the population that is known before with thefollowing criteria: Sharia Bank is aIslamic Bank, the Sharia Bank makesquarterly financial report in 2010-2014 period and has been published in BankIndonesia. Based on the criteria, the sample size is 12 sharia commercial banksThe results showed that Capital Adequacy Ratio (CAR), Net InterestMargin (NIM), Loan to Deposit Ratio (LDR), proved to have significantinfluence on profitability of Sharia Bank(BUS). VariableNonPerformingFinancing (NPF) Financing deposit ratio (FDR), Operational Cost to OperatingIncome (BOPO), inflation and interest rate are not proven to have significantinfluence on profitability of Sharia Bank (BUS). Anova test results (simultaneous)shows the regression model that is built is to meet the criteria fit model. Variationsin bank profitability variables that can be explained by variations of NPL, NIM,LDR and BOPO variables in Sharia (BUS) of 15.7 percent; in Non-ForeignExchange Bank 49.8 percent and the combined Sharia Commercial Bank (BUS)is 50.2 percent